2002
DOI: 10.1136/bjo.86.11.1236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of latanoprost 0.005% and brimonidine tartrate 0.2% on pulsatile ocular blood flow in normal tension glaucoma

Abstract: Aim: To determine the effect of brimonidine tartrate 0.2% and latanoprost 0.005% on pulsatile ocular blood flow (POBF) in patients with normal tension glaucoma (NTG). Method: NTG patients with progressive optic neuropathy, new disc haemorrhage, or field defects that threatened fixation were enrolled into a randomised, investigator masked, crossover study. Group I patients received 4 weeks each of latanoprost, lubricant, and brimonidine, while group II patients received 4 weeks each of brimonidine, lubricant, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 33 publications
(28 reference statements)
0
27
0
1
Order By: Relevance
“…Because blood flow to an organ depends directly on the perfusion pressure, an increase in MOPP could have a beneficial effect on blood flow to the ONH; this effect, however, is regulated by changes in local vascular resistance and occurs only in healthy vascular beds. 54,55 Indeed, in the presence of local vascular dysregulation this beneficial effect could be less evident. 7 Therefore, the clinical significance of MOPP improvement on glaucoma' prognosis requires further clarification.…”
Section: Latanoprost In Treating Poag Patients D Gherghel Et Almentioning
confidence: 99%
“…Because blood flow to an organ depends directly on the perfusion pressure, an increase in MOPP could have a beneficial effect on blood flow to the ONH; this effect, however, is regulated by changes in local vascular resistance and occurs only in healthy vascular beds. 54,55 Indeed, in the presence of local vascular dysregulation this beneficial effect could be less evident. 7 Therefore, the clinical significance of MOPP improvement on glaucoma' prognosis requires further clarification.…”
Section: Latanoprost In Treating Poag Patients D Gherghel Et Almentioning
confidence: 99%
“…In glaucoma patients,1 week to 3 months of topical latanoprost treatment did not affect retinal vessel blood flow, as measured by color Doppler imaging or by fluorescein angiography (as a measure of arterial-venous passage time) (21,23). In contrast, choroidal blood flow in glaucoma patients was increased by up to 20% over the baseline value by topical latanoprost (18,31). Bimatoprost and travoprost have also been evaluated for their effects on ocular blood flow in glaucoma patients, and both positive and negative results have been obtained (1,66).…”
Section: Effects On Ocular Blood Flowmentioning
confidence: 90%
“…Latanoprost significantly increased pulsatile OBF in healthy volunteers, 48,49 and OAG 50,51 and NTG [52][53][54] subjects, although not consistently found. 55 A randomized double-masked crossover study 56 found a more favorable effect on ocular perfusion pressures (OPP) (which are directly related to OBF) with latanoprost than timolol.…”
Section: Other Effectsmentioning
confidence: 99%
“…Head-to-head trials post-dated the study hence studies comparing the medication in question and timolol 71-73, 81,116,119,147,148 or betaxolol 149 were included. In contrast, head-to-head trials, 43,52,53,59,70,76,77,83,[150][151][152][153][154][155][156][157] only were analyzed for the second meta-analysis. 146 The pooled summary estimate significantly favored latanoprost (weighted mean difference (WMD) = 1.10, 95% CI 0.57 to 1.63) over brimonidine.…”
Section: Vs Brimonidinementioning
confidence: 99%